2013
DOI: 10.1007/s11673-013-9454-7
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising a Child-Centric Paradigm

Abstract: Since its inception, donor conception practices have been a reproductive choice for the infertile. Past and current practices have the potential to cause significant and lifelong harm to the offspring through loss of kinship, heritage, identity, family health history and possibly introducing physical problems. Legislation and regulation in Australia that specifies that the welfare of the child born as a consequence of donor conception is paramount may therefore be in conflict with the outcomes. Altering the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In several of these extracts authors problematised moral principles or rules as well as the implementation of those rules and both categories of problematising were not clearly distinguishable. According to Adams (2013), for example, evidence from studies of adult offspring's perceptions that showed that some offspring 'are distressed by procreative choices that their parents were able to make' (Adams 2013, p. 377) provided support for a 'frame-shift' of reproductive freedom: limiting this freedom in agreement with considerations regarding the welfare of the child. The empirical claim, for which several studies were referred to, was that 'the majority of offspring believe that they should know the identity of their donors' (Adams 2013, p. 373).…”
Section: Evidence Used To Problematise a Normative Claimmentioning
confidence: 99%
“…In several of these extracts authors problematised moral principles or rules as well as the implementation of those rules and both categories of problematising were not clearly distinguishable. According to Adams (2013), for example, evidence from studies of adult offspring's perceptions that showed that some offspring 'are distressed by procreative choices that their parents were able to make' (Adams 2013, p. 377) provided support for a 'frame-shift' of reproductive freedom: limiting this freedom in agreement with considerations regarding the welfare of the child. The empirical claim, for which several studies were referred to, was that 'the majority of offspring believe that they should know the identity of their donors' (Adams 2013, p. 373).…”
Section: Evidence Used To Problematise a Normative Claimmentioning
confidence: 99%